Therapy using stem cells for the treatment of chronic kidney failure (Research, Society and Development, 2023)
This study aimed to describe an alternative therapy for patients with Chronic kidney disease (CKD) using stem cells (ST). To carry out this integrative literature review, articles were surveyed in the following databases: PubMed, Scientific Electronic Library Online (Scielo), Coordination for the Improvement of Higher Education Personnel (CIHEP), Virtual Health Library (VHL). The survey took place between the months of February and September 2023. Chronic kidney disease is the result of progressive and irreversible damage to the nephrons and complications, individuals affected by CKD require adaptation in their lifestyle habits, such as following a restrictive diet, continuous use of medications and are dependent on equipment. Renal Replacement Therapies (RRT) are the treatments commonly used for CKD, namely hemolysis or peritoneal dialysis, another way of RRT currently is kidney transplantation. Despite being very effective, these treatments interfere with the quality of life and physical and mental well-being of patients. The effectiveness of treatment for CKD using CT has the great potential to repair kidney injuries, reducing the development and progression of the disease, acting to improve kidney functions. We conclude that stem cells have great potential as therapeutic agents for people with CKD, in animal and pre-clinical studies, however, given this, there is a need for more studies in humans, to prove the viability, safety and efficacy of CT.